A Comparison of 10% Dextrose and 50% Dextrose for the Treatment of Hypoglycemia in the Prehospital Setting. (August 2021) - Weant, Kyle A.; Deloney, Lindsay; Elsey, Grace; Combs, Daniel; French, David
Background: Hypoglycemia is a frequent cause of emergency medical services (EMS) activation; however, limited evidence exists to support optimal prehospital treatment. Objective: This study sought to compare the safety and efficacy of the administration of 10% dextrose (D10) intravenously (IV) versus 50% dextrose (D50) IV for the treatment of hypoglycemia in the prehospital setting. Methods: This was a retrospective cohort study of patients who received IV dextrose by EMS and were transported to an academic teaching hospital emergency department between 2014 and 2017. Results: Four hundred seventy-eight eligible patients were reviewed, with 161 patients receiving D10 and 150 patients receiving D50. There was no significant difference found regarding the need for dextrose retreatment prior to hospital arrival between the D10 and D50 groups (0.6% vs 2.0%; P = .565). The prehospital reassessment glucose in the D50 group was a significantly higher than the D10 group (151.9 vs 124.6 mg/dL, P = .001) and this difference was maintained on hospital arrival (129.5 vs 108.0 mg/dL, P = .011). No significant difference was found between groups with regard to hospital admission, length of stay, or in-hospital mortality. Conclusion: When comparing D10 with D50 for the treatment of hypoglycemia by EMS, there were no significant differences in the need for dextrose retreatment prior to hospital arrival. The use of D50 resulted in a significantly higher blood glucose concentrations both in the prehospital setting and upon hospital arrival. Further study is needed in larger patient populations to evaluate the use of D10, the need for dextrose readministration, and its impact on clinical outcomes.